2013
DOI: 10.1098/rspb.2013.1046
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural circuits underlie assessment of a diversity of natural dangers by American crows

Abstract: Social animals encountering natural dangers face decisions such as whether to freeze, flee or harass the threat. The American crow, Corvus brachyrhynchos, conspicuously mobs dangers. We used positron emission tomography to test the hypothesis that distinct neuronal substrates underlie the crow's consistent behavioural response to different dangers. We found that crows activated brain regions associated with attention and arousal (nucleus isthmo-opticus/locus coeruleus), and with motor response (arcopallium), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…That crows responded most strongly to a predator with a conspecific prey is consistent with a previous study on crows (Barash, 1976) and with responses by herring gulls, Larus argentatus, and lesser blackbacked gulls, Larus fuscus (Kruuk, 1976). In crows, exposure to a hawk results in activation of the caudal nidopallium (Cross et al, 2013), a region of the brain proposed to be important in decision making such as fleeing or mobbing (Güntürkün, 2005). Our finding that crows were less likely to mob if a hawk was observed without conspecific prey supports the conclusion that crows are sensitive to predator behaviour (with or without prey) and subsequently adjust the aggressiveness of their mobbing response.…”
Section: Experiments 1: Crow Response To a Dead Conspecific And/or A Psupporting
confidence: 90%
See 2 more Smart Citations
“…That crows responded most strongly to a predator with a conspecific prey is consistent with a previous study on crows (Barash, 1976) and with responses by herring gulls, Larus argentatus, and lesser blackbacked gulls, Larus fuscus (Kruuk, 1976). In crows, exposure to a hawk results in activation of the caudal nidopallium (Cross et al, 2013), a region of the brain proposed to be important in decision making such as fleeing or mobbing (Güntürkün, 2005). Our finding that crows were less likely to mob if a hawk was observed without conspecific prey supports the conclusion that crows are sensitive to predator behaviour (with or without prey) and subsequently adjust the aggressiveness of their mobbing response.…”
Section: Experiments 1: Crow Response To a Dead Conspecific And/or A Psupporting
confidence: 90%
“…Crows are highly sensitive to human aggression even to the extent that they are attentive to gaze (Clucas, Marzluff, Mackovjak, & Palmquist, 2013) and can learn and recall human faces after being captured by them (Marzluff et al, 2010). Cross et al (2013) found that the sight of a novel person holding a dead crow stimulated activation of the dorsomedial portion of the hippocampus and part of the cerebellum, areas consistent with danger learning. However, in Cross et al's study, crows were tested in isolation, where they could not mob and did not vocalize.…”
Section: Experiments 1: Crow Response To a Dead Conspecific And/or A Pmentioning
confidence: 97%
See 1 more Smart Citation
“…Low head position during feeding, for example, can reduce the ability to detect predators (Bednekoff and Lima, 2005). A reduction in the rate of blinking might also be a means to reduce the cost of intermittent blinking in riskier settings (Cross et al, 2013;Yorzinski, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the Hp plays a critical role in affective and cognitive processes, including spatial memory, in both birds and mammals (Atoji & Wild 2006;Leuner & Gould 2010;Jinno 2011a), and these functional differences are represented in different subdivisions within the Hp (Atoji & Wild 2006;Atoji et al 2016). The avian Hp is associated with cognitive skills including homing, food storage and retrieval, migration and imprinting Bingman & Mench 1990;Clayton 1995b;Broadbent et al 2004;Pravosudov et al 2006;LaDage et al 2009), but is also part of the limbic network which underlies emotionally driven learning, motivation and memory of social signals (Cheng et al 1999;Bailey et al 2002;Cross et al 2013). Therefore, it is not surprising that the avian Hp is divided into sub-regions, as is the case in the mammalian Hp.…”
Section: Introductionmentioning
confidence: 99%